2017
DOI: 10.1002/adom.201700069
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Nanoparticles with Hot Spots for Plasmon‐Induced Circular Dichroism of Chiral Molecules in the UV Spectral Interval

Abstract: absorb and scatter visible light and, furthermore, plasmonic NCs are known for their strong local enhancement of electromagnetic fields. When a chiral biomolecule is attached to a nonchiral metal NC, the chiral response of a biomolecule becomes transferred to the plasmonic NC via near-field dipolar and multipolar interactions. [4,5] Circular dichroism spectroscopy, which quantifies the difference between the assembly's responses to left and right circularly polarized light, is a well-established experimental m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 52 publications
1
50
0
Order By: Relevance
“…The modeling of chiral media relies on proper formalism of the material's properties, especially the chiral parameter κ. Here, we adopt the convenient expressions derived by Govorov and coworkers: 25,26…”
Section: Enhancing CD By Chiral Hotspotsmentioning
confidence: 99%
“…The modeling of chiral media relies on proper formalism of the material's properties, especially the chiral parameter κ. Here, we adopt the convenient expressions derived by Govorov and coworkers: 25,26…”
Section: Enhancing CD By Chiral Hotspotsmentioning
confidence: 99%
“…This field has attracted significant interest over the last years, not only because of the fundamental importance of chirality in nature but also because of the strong and tunable chiroptical response in plasmonic systems. [ 45–52 ] Optical chirality, that is, the different response of a system to left and right circularly polarized light (LCP, RPC, respectively), is an intrinsically 3D property that requires advanced fabrication strategies. [ 53–55 ] Also, it was shown that even minute changes to the morphology result in sizable changes in the chiroptical response, [ 56 ] further underlining the fabrication challenges and the requirement of high accuracy planar and 3D nanofabrication.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting, yet under explored aspect of anisotropic nanostructures is the differential absorbance, Δ A , that is associated with the dichroic (linear or circular) properties of the structure. By exploiting the improved sensitivity offered by a plasmon‐enhanced Δ A measurement, the local molecular anisotropy of an adsorbed analyte can be probed . Furthermore, it may be possible to induce local anisotropy to the analyte through the interaction between the adsorbed analyte and a locally polarized plasmon.…”
Section: Introductionmentioning
confidence: 99%